2007
DOI: 10.1021/jp072539q
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Photoluminescence Properties of MgO Microtubes Synthesized from Hydromagnesite Flowers

Abstract: Monoclinic hydromagnesite (Mg 5 (CO 3 ) 4 •(OH) 2 •4H 2 O) flower-like structures of 2-3 µm diameter have been synthesized at room temperature by a simple precipitation method without using any template, catalyst, or surfactant. The as-synthesized flowers were further calcined at various temperatures to prepare monodispersed, nanofibrous MgO microtubes of aspect ratio ∼15. Both the precursor flowers and the MgO microtubes formed were characterized by powder XRD, TG-DTA, FT-IR, SEM, EDAX, HR-TEM, SAED, BET anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
64
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(71 citation statements)
references
References 48 publications
7
64
0
Order By: Relevance
“…Thus, if the defect concentration is more, the luminescence intensity also will be more. In general, change in the lattice parameter can be correlated with the concentration of the defects in any undoped material as reported by Janet et al [27]. The observed increase in the luminescence of sample A (spectrum a) was in good agreement with the lattice parameter value calculated from the XRD data.…”
Section: Photoluminescence (Pl) Studiessupporting
confidence: 82%
See 2 more Smart Citations
“…Thus, if the defect concentration is more, the luminescence intensity also will be more. In general, change in the lattice parameter can be correlated with the concentration of the defects in any undoped material as reported by Janet et al [27]. The observed increase in the luminescence of sample A (spectrum a) was in good agreement with the lattice parameter value calculated from the XRD data.…”
Section: Photoluminescence (Pl) Studiessupporting
confidence: 82%
“…The absorption peak of sample B (spectrum b) undergoes a red shift for H 2 O molecule (from 3448 to 3422 cm −1 and from 1639 to 1633 cm −1 ) and becomes weaker when compared with sample A (spectrum a), indicating the reduction in the degree of binding of H 2 O on the surface of bigger crystallites due to the reason that they have less atoms/surface unit for the binding interaction with H 2 O molecules. In addition, a weak band corresponding to the adsorption of gas-phase CO 2 is visible at around 2375-2385 cm −1 and CO 3 2− is visible at around 1430-1440 cm −1 for both sample A (spectrum a) and B (spectrum b) [27]. However in spectrum (b), the bands are weakened and a red shift is observed for both CO 2 and CO 3 2− stretching frequency from 2383 to 2377 cm −1 and 1439 to 1436 cm −1 respectively, indicating progressive reduction in the degree of binding of CO 2 and CO 3 2− molecules at the bigger crystallites.…”
Section: Fourier Transform Infrared (Ft-ir) Analysismentioning
confidence: 96%
See 1 more Smart Citation
“…When mixing MgCl 2 ·6H 2 O with Na 2 CO 3 solution, a white precipitate was formed immediately. [33] The SEM image shown in part A of Figure 1 revealed that the white precipitate is a pillarlike structure of about 30 μm in length and 800 nm in diameter. The surface of the pillar is smooth.…”
Section: Resultsmentioning
confidence: 98%
“…Bands corresponding to the water of crystallization are observed around 3517 and 3451 cm −1 . Free O-H vibration band is observed around 3650 cm −1[39]. InFig.…”
mentioning
confidence: 86%